2010
DOI: 10.1007/s11105-010-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Water Deficit Stress Upregulated Genes in Sugarcane

Abstract: Sugarcane represents an important renewable source among biofuel crops with high capability to assimilate carbon among the C4 plants. Limited availability of freshwater renders this crop uneconomical, warranting the necessity for the development of varieties with higher water use efficiency and tolerant to water deficiency stress. Sugarcane variety cv. Co740 was subjected to varied levels of water deficiency stress to isolate transcripts differentially expressed to the imposed stress. The leaf relative water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 58 publications
0
50
0
4
Order By: Relevance
“…Among these environmental factors, water deficiency and salinity are the major abiotic factors limiting sugarcane production (Menossi et al 2008), demanding efforts to investigate the adaptation and tolerance mechanisms of stress at the molecular level. In our earlier study, a suppression subtractive hybridization (SSH) approach was used to isolate ESTs upregulated during water-deficit stress in sugarcane and elucidate their transcriptional regulatory mechanisms (Prabu et al 2011). Among the genes identified, a waterdeficit stress-specific cDNA, ScMYBAS1 (accession no.…”
Section: Introductionmentioning
confidence: 99%
“…Among these environmental factors, water deficiency and salinity are the major abiotic factors limiting sugarcane production (Menossi et al 2008), demanding efforts to investigate the adaptation and tolerance mechanisms of stress at the molecular level. In our earlier study, a suppression subtractive hybridization (SSH) approach was used to isolate ESTs upregulated during water-deficit stress in sugarcane and elucidate their transcriptional regulatory mechanisms (Prabu et al 2011). Among the genes identified, a waterdeficit stress-specific cDNA, ScMYBAS1 (accession no.…”
Section: Introductionmentioning
confidence: 99%
“…The SSH technique is believed to generate an equalized representation of differentially expressed genes and provides a high enrichment of differentially expressed mRNA (Diatchenko et al 1996;Marenda et al 2004). The efficiency and reproducibility of SSH are very useful in studies of tissue-specific, developmental, or induced differentially expressed genes (Von Stein et al 1997;Basyuni et al 2011;Prabu et al 2011;Yang et al 2011b). In addition, in some plant species, SSH has proved useful for identifying genes differentially expressed during zygotic and somatic embryogenesis (Bishop-Hurley et al 2003;Namasivayam and Hanke 2006;Legrand et al 2007;Tsuwamoto et al 2007;Wang et al 2007;Geng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abscisic acid (ABA) (Kholová et al, 2010), the pH (Schachtman & Goodger, 2008) and the ionic distribution (Bahrun et al, 2002) seem to play an important role on signaling throughout the plant under water stress. Molecular studies have identified a wide range of genes expressed by sugarcane plants under water stress conditions (Iskandar et al, 2011;Prabu et al, 2010;Rodrigues et al, 2011). Regarding the responses to stress, signaling pathways regulated by hormones are highly drought-responsive, mainly those associated with the increased ABA synthesis (Pinheiro & Chaves, 2011).…”
Section: Physiological Parameters In Sugarcanementioning
confidence: 99%